Factors Causing Anemia in Pregnant Women: A Narrative Review with Systematic Elements - Rahmiwati, Anita; Putri Sabila, Virgina (Department of Nutrition, Faculty of Health Sciences, Universitas Brawijaya Malang, 2025)
Anemia is a significant health problem among pregnant women and is associated with complications such as low birth weight, delivery risks, and high maternal and infant morbidity. The prevalence of anemia among pregnant women in Indonesia remains high. This review aimed to identify and synthesize factors influencing anemia in pregnant women through a systematic review approach. A systematic search was conducted in PubMed, ScienceDirect, and Google Scholar for articles published between 2019 and 2024 using the keywords “causing factors” OR “anemia” OR “pregnant women.” A total of 1,963 records were identified, 1,212 screened, 467 full-text articles assessed for eligibility, and 6 studies were finally included. The included studies reported anemia prevalence ranging from 24.1% to 83.5%. Quantitative findings indicated significant associations between anemia and delayed first ANC visit in the third trimester (OR = 10.42; CI: 4.27-25.4), history of anemia before pregnancy (OR = 4.64), living in urban areas (OR = 1.8), low income with inadequate dietary diversity (OR = 1.94), inadequate vegetable intake (OR = 2.62), meat (OR = 2.71), eggs (OR = 2.98), fish (OR = 2.38), lack of formal education (OR = 3.86), non-use of iron tablets (OR = 2.64), Plasmodium vivax infection (OR = 7.58), and chronic energy deficiency (OR = 12.75-24). These risk factors were categorized into internal factors (maternal age, gestational age, parity, pregnancy spacing, nutritional status), external factors (iron supplementation, antenatal visits, nutritional intake/consumption), and sociodemographic factors (economic status, education level). Maternal age, gestational age, poor compliance with iron supplementation, and inadequate nutritional intake were the most consistently associated with anemia.